Beyond Majors: Exploring the Diversity of Learning Styles Among University Students in English Foreign Language Classroom - Wardani, Niasisca Agustia (Proceedings Series on Social Sciences & Humanities, 2025)
Despite a growing body of research on learning styles in English as a Foreign Language (EFL) contexts, a significant gap remains on understanding the learning styles of university students. While primary and secondary education have been well-studied, the unique academic demands, learning environments, and motivations of university students have been largely overlooked, potentially hindering effective teaching and student success. Recognizing the continued relevance of learning styles in higher education, this study aimed at investigating the learning styles of non-English University students in Englih classroom through a descriptive quantitative design. Guided by Neil Fleming's VARK framework, the study combines questionnaire data on students’ self-reported learning style preferences with classroom observations of actual learning behaviors of 31 respondants. The data were analyzed using descriptive statistics. Results revealed a diverse range of learning styles among the participants. Notably, a majority (over 50%) displayed a preference for multimodal style, followed by kinesthetic, auditory, and read-write styles. However, classroom observations portrayed a contrast, with students predominantly relying on their single preferred style in response to the limited range of teaching activities offered. This suggests a potential mismatch between students' diverse learning styles and the pedagogical methods employed. Further, these results hold valuable implications for EFL teachers to highlight the need of providing English courses that incorporate a variety of teaching methods and activities that are customized to students' different learning styles.